Psychological Profile of English Pedagogy Students: Attributional Styles, Academic Self-Concept and Self-Esteem - Angélica Vera Sagredo; Héctor Vega Pinochet (CUHSO)
This article examines the relationship between attributional styles, academic self-concept and self-esteem in university students of English Pedagogy. Their profiles in these variables were identified by using a quantitative descriptive-correlational approach and a sample of 125 students. In order to fulfill the objective of the study, descriptive and comparative analyses were performed through T Student and ANOVA. Also, Pearson correlations were performed to identify the link between the dimensions of the instruments with respect to the sociodemographic variables. The results showed that students tend to attribute their failures to lack of effort, lack of ability and moderate academic self-efficacy. Females evidenced greater attribution of failure due to lack of ability and family conflicts. Correlations were found between several dimensions, highlighting the negative relationship between internal causes and lack of effort. These findings provide relevant information for future educational interventions in this population.